COMPARATIVE EVALUATION OF THREE RECTAL PALATATION BASED ESTRUS SYNCHRONIZATION PROTOCOLS AT FIELD LEVEL IN RAJASTHAN BUFFALOES (Indian Journal of Animal Production and Management, 2014)
Three different estrous synchronization protocols were evaluated. Treatment included an injection of prostaglandin (PGF2α;1 ml VSM - Vulva-sub mucosal route) on palpation of CL; status of the estrous cycle was evaluated by rectal palpation and addition of gonadotropin releasing hormone (GnRH 2.5ml), fixed time insemination (FTAI) was done 72 h post PGF2α injection. Similar was the second protocol in which, in gonadotropin releasing hormone (GnRH; 2.5 ml.) 7 days addition to PGF2α ; 1 ml VSM administration and 9 days GnRH; 2.5 ml was administered 48 h post PGF2α ; 1 ml VSM injection and FTAI was done. For the third protocol, GnRH treated buffaloes were observed for 7 days and then PGF2α; 14 days injection and GnRH;16 days was administered and at the time of A.I. Three different groups of animals were maintained for three different protocols respectively. Statistical data analysis (using chi-square) showed that first and second protocol have been found significantly (P
Keywords: Estrus; Synchronization; GnRH; PGF2α; Buffaloes; Reproduction